Research on network programmable technologies - Lijun XIE; Yuxiang HU; Binqiang WANG; Julong LAN; Guozhen CHENG; Zhiming WANG (Dianxin kexue)
Network programmable technologies enforce the capacity of flexible configuration and resource composition by providing network devices with programmable interfaces. Starting with the discussion on the background in the naissance and developments of network programmable technologies，the initial programmable technologies，frameworks of control and data plane and typical software defined networking （SDN）and network function virtualization（NFV）were reviewed. The research on protocol irrelevance，implementation of flow tables， high-level programming languages and integration with NFV were elaborated. Moreover，the future works were summarized in the end.